Verse writing in schools - Bolton, Eric J. (Commonwealth and international library, 1966)
Verse Writing in Schools presents methods in creative writing that can be used in English classes in the same way as a grammar textbook. The book focuses on the teaching and appreciation of poems to children new to poetry writing